Honor, Build, and Restructure - Linsay DeMartino; Dianne Gardner Renn (Impacting Education, 2023)
School leaders enrolled in CPED-influenced and practitioner focused doctoral programs require specific research-based skills and knowledge that bridge both educational scholarship and practice in order to be relevant for both their dissertation process and school practice. In doing so, these doctorate in education (EdD) programs must critically exam their qualitative research methods courses to honor the professional practice of their adult learners and usher in innovative, collaborative, transformative, and participatory research design courses to meet this demand. As such we present our methodological course sequence built on principles of adult learning and a signature pedagogy, the first course is a reimagination of the qualitative research course and the second is a reconceptualized transformative capstone.